New forms of employment and labour protection in China - Tu Wei; Wang Xueyu (International Labour Organization (ILO), 2024)
In recent years, China's labour market has seen a significant rise of the new forms of employment, which differs in scale, type, and function compared to the developed economies. This study focuses on four emerging forms of the new employment patterns in China, including app-based gig work, micro-task crowdsourcing, prosumer work, and platform outsourcing to individuals, particularly examining their diversity, scale, development, and the status quo of the labour protection. Additionally, the paper summarises the challenges faced by the labour law and policy in the digitalisation era in China, as well as the government and social partners' innovative measures to address them.
Keywords: 330; informal employment; self employment; non-standard forms of employment; employment policy; employment services